Is Antibiotic Prophylaxis Necessary Before Dental Procedures in Patients Post Total Ankle Arthroplasty?. (February 2019) - Noori, Naudereh; Myerson, Charles; Charlton, Timothy; Thordarson, David
Background: The need for dental antibiotic prophylaxis after orthopedic surgery remains unclear. Current recommendations are based on patients with total hip and total knee arthroplasties. We investigated available evidence regarding the need for dental antibiotic prophylaxis in patients post foot and ankle surgery, specifically total ankle arthroplasty. Additionally, we examined the microbiology behind the risk of transient bacteremia from dental procedures and whether this leads to an increased risk for postoperative infection in foot and ankle surgery. Methods: We performed a MEDLINE literature review of English articles between 1980 and 2018 on patients with prosthetic joints undergoing dental work, and studies evaluating hematogenous prosthetic joint infection (PJI) and dental antibiotic prophylaxis. We additionally included articles on PJI post total ankle arthroplasty, as well as committee guidelines. Results: There is no literature at present that evaluates transient bacteremia with dental procedures in patients following foot and ankle surgery. The data on this topic are isolated to PJI rates in the context of hip and total knee arthroplasty. This is of particular interest as rates of total ankle arthroplasty PJI have been reported to be 2- to 4-fold higher than in hip and total knee arthroplasty. Conclusion: The concern for postoperative infection due to transient bacteremia without dental antibiotic prophylaxis can be extrapolated to patients undergoing foot and ankle surgeries. Some data suggest that oral cavity bacteria can seed a prosthetic joint, though no clear relationship has been demonstrated. Similar risk factors have been identified between hip and knee PJI and total ankle arthroplasty. In light of the absence of scrutiny of and guidelines on this topic in foot and ankle surgery, it may be advisable to apply similar principles to decision-making in patients after foot and ankle surgery. Level of Evidence: Level III, systematic review.